Factors Affecting Online Shopping Behavior: Case Study on Palestinian Students - Daana, Abdalnasser N. N.; Dana, Rawya Nazmi (كلية الإمارات للعلوم التربوية, 2023)
This research aims to investigate the factors affecting consumers' online shopping behaviors. The main variables tested are brand recognition, web interface design and demographics. This study was conducted as a case study on students of the college of administrative sciences and information system at Palestine Polytechnic University; a sample of 178 students were surveyed online in order to test the hypothesis from a population of a total of 1000 students of the college, using a random sampling method. In this research, an order quantitative approach was applied to do the correlation analysis. The measures of analysis were Cronbach's Alpha Reliability test, Pearson's Correlation Matrix and Linear Regression Analysis. The main finding of the research is that there is a significant impact that brand recognition has on a consumer's online shopping behavior, as well as the significant impact of the webinterface design and consumer age. The study has also found that gender, specializations, and family income have no significant impact on the consumer online shopping behavior. The finding of this research should be considered by companies that operate online to better fine-tune their marketing decisions, whereas many other variables that are also influencing consumers' online shopping should be investigated by future research.
Keywords: السلوك التسويقية -- الانترنت -- العلامات التجارية -- التجارة الإلكترونية